Near-Infrared-Excitable Organic Ultralong Phosphorescence through Multiphoton Absorption - Ye Tao; Lele Tang; Qi Wei; Jibiao Jin; Wenbo Hu; Runfeng Chen; Qingqing Yang; Huanhuan Li; Ping Li; Guichuan Xing; Quli Fan; Chao Zheng; et al. (Research, 2020)
Organic ultralong room-temperature phosphorescence (OURTP) with a long-lived triplet excited state up to several seconds has triggered widespread research interests, but most OURTP materials are excited by only ultraviolet (UV) or blue light owing to their unique stabilized triplet- and solid-state emission feature. Here, we demonstrate that near-infrared- (NIR-) excitable OURTP molecules can be rationally designed by implanting intra/intermolecular charge transfer (CT) characteristics into H-aggregation to stimulate the efficient nonlinear multiphoton absorption (MPA). The resultant upconverted MPA-OURTP show ultralong lifetimes over 0.42 s and a phosphorescence quantum yield of ~37% under both UV and NIR light irradiation. Empowered by the extraordinary MPA-OURTP, novel applications including two-photon bioimaging, visual laser power detection and excitation, and lifetime multiplexing encryption devices were successfully realized. These discoveries illustrate not only a delicate design map for the construction of NIR-excitable OURTP materials but also insightful guidance for exploring OURTP-based nonlinear optoelectronic properties and applications.